Analysis Of Caring Clinical Supervisors On The Adaptation Of Practicing Students In The Hospital TK IV DKT Kediri City - Alfian Fawzi,; Adriani Marince Un,; Lingga kusuma wardhani,; Aprin rusmawati, (Journal of Health Science Community, 2025)
The lack of caring between clinical supervisors and practicing students causes students to feel unnoticed and there is no attitude of helping and providing support, causing students to feel reluctant to undergo practice. The purpose of this study was to determine the effect of caring clinical supervisors on the adaptation of practicing students at TK IV DKT Kediri Hospital. This research design is correlational with a cross-sectional approach. Respondents were taken using an accidental sampling technique with a sample of 37 people. The independent variable is caring clinical supervisors and the dependent variable is the adaptation of practicing students. Statistical test results using ordinal regression. The results showed that caring clinical supervisors were known to be almost half of the respondents as many as 15 (40.5%) in the good category. Adaptation of practicing students is known to most respondents as many as 21 (56.0%) in the good category. The results of data analysis show that the significance level is 0.000< α= 0.05 so H0 is rejected and H1 is accepted, thus there is an effect of caring clinical supervisors on the adaptation of practicing students. The Pseudo R- Square result on the Nagelkerke value is 0.635 or 63.5%. Based on the results of the study, it can be concluded that there is an effect of caring clinical supervisors on the adaptation of practicing students. Clinical supervisors who behave caring will increase positive feelings in students so that they can adapt during clinical practice. It is recommended that clinical supervisors not only act as educators but are expected to be able to assist and socialize with their new roles and be able to know the learning needs of students.